Original paperEffects of bladder distension on dose distribution of vaginal vault brachytherapy in patients with endometrial cancer - Guler, Ozan C.; Onal, Cem; Acibuci, Ibrahim (Journal of Contemporary Brachytherapy, 2014)
Purpose : To investigate dosimetric effects of bladder distention on organs at risk (OARs) during treatment of endometrial cancer using 3D image-based planning of postoperative vaginal vault brachytherapy (BRT). Material and methods : Fifteen patients with early-stage endometrial cancer were studied, each undergoing adjuvant BRT of vaginal vault via 3.5 cm diameter cylinder. As treatment, 25 Gy in 5 fractions were delivered to 5 mm depth of the vaginal mucosa. Dose-volume histograms of OARs were generated individually with bladder empty and with bladder inflated by sterile saline (180 ml), to compare doses received. Results : Bladder distention appreciably impacted dosimetry of bladder, sigmoid colon, and small bowel, but dosimetry of rectum was unaffected. With bladder inflated, mean cylinder-to-bowel distance increased significantly (1.69 cm vs. 1.20 cm; p = 0.006). Mean minimum dose to most exposed 2 cc (D 2cc ) volume also rose significantly at bladder (5.40 Gy vs. 4.55 Gy [18.7%]; p < 0.001), as opposed to near-significant reductions in D 2cc at sigmoid colon (15.1%; p = 0.11) and at small bowel (10.5%; p = 0.14). A full bladder had no effect on dose to 50% volume (D50%) of bladder or rectum, and declines seen in mean D50% values of sigmoid colon (22.7%; p = 0.12) and small bowel (19.0%; p = 0.13) again fell short of statistical significance. Conclusions : The combination of a full bladder and an empty rectum may cause significant unwanted increases in BRT dosing of bladder, without significantly impacting sigmoid colon and small bowel exposures. These findings should be validated through further clinical studies.